1997
DOI: 10.1002/(sici)1097-0142(19970315)79:6<1077::aid-cncr4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and metachronous primary gastric lymphoma and adenocarcinoma

Abstract: RESULTS.Two different tumors were found synchronously in 10 patients (5 with Masatoshi Fujishima, M.D. 2 independent tumors and 5 with contiguous/collision tumors) and metachronously in 2. The size of the lymphomas (mean, 7.2 cm) was larger than that of the adeno-1 Second Department of Pathology, Faculty of carcinomas (mean, 3.6 cm) (P õ 0.005). Histologically, 9 of the 12 lymphomas Medicine, Kyushu University, Fukuoka, Japan.(75%) were mucosa-associated lymphoid tissue lymphomas, and all lymphomas 2 Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 38 publications
3
61
1
1
Order By: Relevance
“…Furthermore, EBV infection in such cases is extremely rare; to our knowledge only two cases of EBV-GC coexistent with gastric lymphoma have been reported. One was lymphoepithelioma-like carcinoma with mucosa-associated lymphoid tissue (MALT) lymphoma [8], and the other was a poorly differentiated adenocarcinoma with low-grade Tcell lymphoma of pleomorphic small cell type [15]. Besides the EBV-infected cancer cells, H. pylori infection was also observed in the previously reported two cases [8,15].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Furthermore, EBV infection in such cases is extremely rare; to our knowledge only two cases of EBV-GC coexistent with gastric lymphoma have been reported. One was lymphoepithelioma-like carcinoma with mucosa-associated lymphoid tissue (MALT) lymphoma [8], and the other was a poorly differentiated adenocarcinoma with low-grade Tcell lymphoma of pleomorphic small cell type [15]. Besides the EBV-infected cancer cells, H. pylori infection was also observed in the previously reported two cases [8,15].…”
Section: Discussionmentioning
confidence: 94%
“…Coexistence of primary gastric lymphoma and carcinoma is extremely uncommon. Nakamura et al [15] reported that its incidence accounts for only 0.098% of all examined gastric carcinomas (nine of 9,150 cases). Furthermore, EBV infection in such cases is extremely rare; to our knowledge only two cases of EBV-GC coexistent with gastric lymphoma have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations